1997
DOI: 10.1021/ic9701827
|View full text |Cite
|
Sign up to set email alerts
|

Selective Platination of Biologically Relevant Polyamines. Linear Coordinating Spermidine and Spermine as Amplifying Linkers in Dinuclear Platinum Complexes

Abstract: A new approach to the synthesis of novel bifunctional dinuclear platinum complexes with linear coordinating spermidine and spermine is reported. The synthetic pathway involves first the three-step selective protection of the polyamines, giving bis(trifluoroacetyl)polyamines (1, 4), (tert-butoxycarbonyl)bis(trifluoroacetyl)polyamines (2, 5), and (tert-butoxycarbonyl)polyamines (3, 6), respectively. The platination at desired sites with activated species of cis- or trans-[PtCl2(NH3)2] (CDDP or TDDP, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 33 publications
2
120
0
1
Order By: Relevance
“…These chemical shifts are consistent with similar metal complexes with PtN 3 Cl coordination spheres, where N = two trans-ammine ligands and one primary amine ligand. [16,17] Figure 1. 195 Pt NMR spectrum (top), 1 H NMR spectrum (middle) and ESI mass spectrum (bottom) of HLSP-6.…”
Section: Resultsmentioning
confidence: 99%
“…These chemical shifts are consistent with similar metal complexes with PtN 3 Cl coordination spheres, where N = two trans-ammine ligands and one primary amine ligand. [16,17] Figure 1. 195 Pt NMR spectrum (top), 1 H NMR spectrum (middle) and ESI mass spectrum (bottom) of HLSP-6.…”
Section: Resultsmentioning
confidence: 99%
“…BOC-protected spermidine and spermine complexes of this type are well-known as direct precursors in the synthesis of the free polyamine drugs 1,1/ t,t-spermidine and 1,1/t,t-spermine, respectively. 5 These blocked polyamine-bridged complexes are 2-3 orders of magnitude less cytotoxic than the unprotected analogues containing the protonated quaternary nitrogens. Release of the active species can be achieved through spontaneous, pH dependent hydrolysis of the blocking groups.…”
Section: Introductionmentioning
confidence: 99%
“…[6,15,17,18] In addition, it was verified that linkage of some of these molecules to previously tested anticancer drugs leads to a higher cytotoxic effect and, in some cases, even to an enhancement of the efficacy of the long-used first-generation drug cisplatin [cis-diamine dichloroplatinum(II)]. [19][20][21][22][23][24][25][26][27] Recently, it was also demonstrated that polyamines may exert insulinlike activity by interacting with receptors on fat-cell membranes. [28] Despite the vital role of polyamines in living cells, little is known about their structure at a molecular level.…”
Section: Introductionmentioning
confidence: 99%